An accurate and efficient measure of welfare tradeoff ratios - Wenhao Qi; Edward Vul; Lindsey J. Powell (PLoS ONE, 2025)
People’s decisions are affected by their interest in others’ welfare. They can be motivated both to help and to harm others. The direction and magnitude of these motivations can be quantified relative to a person’s self-interest as a welfare tradeoff ratio (WTR). This construct is valuable for testing quantitative theories of social motivation. However, most existing measures of WTRs, and the similar construct of social value orientation (SVO), are based on multiple choices between discrete sets of payoffs, which forces a tradeoff between the accuracy and efficiency of the measures. Here we introduce the Lambda Slider, a WTR measure that is simultaneously accurate and efficient. A participant uses a linear slider to choose from a continuous range of payoff allocations for herself and her social partner. The underlying payoff functions for self and other create a one-to-one correspondence between the participant’s potential WTR values and the slider positions that she could choose, which enables accurate measurements of WTR from a single response. Across three experiments, we show that a single response on the Lambda Slider has high reliability, high convergent validity with other measures of social motivation, and high external validity for an altruistic decision with real-world consequences. The Lambda Slider is easy to implement and can be applied in a wide variety of studies on the forces that shape social motivation.